Notas sobre a crítica de Hegel ao subjetivismo na filosofia prática: liberdade e normatividade - Lima, Erick (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: Hegel’s practical philosophy might be better analyzed if considered in the light of the modern debate on the conception of freedom as self-determination. To begin with, the paper aims at presenting ral guidelines Hegel’s critique on Fichte, in order to indicate how Hegel´s theory of practical freedom is motivated to respond to the challenge of thinking self-determination less unilaterally (1). Then I attempt to comprehend Hegel´s notion of right in the context of the issues created by political modernity, and I conclude by showing the influence of Hegel´s notion of right in the conceptual framework of practical philosophy (2).